2012
DOI: 10.1007/s12032-011-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel serological tumor markers for human prostate cancer using integrative transcriptome and proteome analysis

Abstract: The aim of this study was to identify novel serological tumor markers for human prostate cancer (PCa). We compared the gene expression profile of PCa tissues to adjacent benign tissues of prostate using gene expression microarray. 1207 genes that were consistently different from adjacent benign tissues of prostate (paired t test, P<0.05) were selected as differentially expressed genes (DEGs). Among them, 652 DEGs were upregulated in PCa, whereas 555 DEGs were downregulated in PCa. In addition, two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
3
33
1
Order By: Relevance
“…To identify statistically significant biochemical recurrence courses, recursive partitioning was performed on a single gene expression profile using the ‘party’ package from CRAN (Han et al, 2012) with accompanying biochemical recurrence data taken from (Glinsky et al, 2004, Taylor et al, 2010). Kaplan Meier plots of the risk of biochemical recurrence were produced using the ‘survival’ package and p-values from the log rank test were corrected using the Bonferroni correction method.…”
Section: Methodsmentioning
confidence: 99%
“…To identify statistically significant biochemical recurrence courses, recursive partitioning was performed on a single gene expression profile using the ‘party’ package from CRAN (Han et al, 2012) with accompanying biochemical recurrence data taken from (Glinsky et al, 2004, Taylor et al, 2010). Kaplan Meier plots of the risk of biochemical recurrence were produced using the ‘survival’ package and p-values from the log rank test were corrected using the Bonferroni correction method.…”
Section: Methodsmentioning
confidence: 99%
“…What's more, HnRNP-L can reportedly regulate the tumorigenic capacity of lung cancer [14, 15]. Furthermore, using two-dimensional electrophoresis and mass spectrometry, Zhao et al showed that HNRNP-L is differentially expressed in Pca [16]. However, the specific roles of HnRNP-L in Pca remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of 2D-DIGE-based proteomics focused to identify novel clinically relevant proteins in PCa (24)(25)(26). In the present study, compared with normal prostate epithelial cells, eleven differentially expressed proteins were identified as potential candidates associated with prostate cancer metastases.…”
Section: Discussionmentioning
confidence: 80%